Nilai Yang Dirasakan dan Loyalitas Pelanggan: Peran Kepuasan Sebagai Pemediasi - Muhammad Rizki Syahputra; Miftahul Jannah (Jurnal Kajian Ilmu Manajemen (JKIM), 2026)
This study aims to determine the effect of Customer Perceived Value on customer loyalty with customer satisfaction as a mediating variable at Kedai Poenya Kita in Jombang. The research method used is quantitative with a descriptive approach. The data were obtained through distributing questionnaires to 100 respondents and analysed using Structural Equation Modeling (SEM) techniques with the help of SmartPLS 4 software. The results showed that Customer Perceived Value has a positive and significant effect on customer satisfaction, as well as customer loyalty. In addition, customer satisfaction also has a positive and significant effect on customer loyalty. Other findings reveal that customer satisfaction is able to partially mediate the relationship between Customer Perceived Value and customer loyalty. Thus, increasing customer value perceptions of the products and services provided can increase satisfaction while strengthening customer loyalty to Kedai Poenya Kita.